Pyrolysis of Medical Mask Waste into Liquid Fuel Using Activated Natural Zeolite Catalyst - Fitria Yulistiani; Risdo Satriya Agati; Aria Henry Haidar; Ayu Ratna Permanasari (Fluida, 2024)
Due to the COVID-19 pandemic, there has been a rise in the amount of mask waste, which can be recycled using catalytic pyrolysis. The method targets polypropylene, the primary material used in mask production, and utilizes activated natural zeolite as a catalyst. This process can enhance the selectivity of oil product compounds such as benzene, toluene, ethyl benzene, and xylene. This research aims to investigate the impact of the Catalyst Feed mass ratio (C/F) and time on the distribution and recovery of oil products and to identify the optimal operating conditions for generating oil products comparable to the gasoline fraction. The steps are preparation, activation of zeolite catalysts, pyrolysis, component distribution analysis, and pyrolytic oil physical properties test. The variations in this study are C/F of 0.05, 0.1, and 0.2; and pyrolysis times of 30 and 60 minutes. Increasing the C/F to 0.2 reduced the oil yield to 41.18 %w/w, while increasing the time to 60 minutes reduced the char yield to around 3 %w/w. Pyrolysis at C/F = 0.05 for 30 minutes produced the highest monoaromatic composition of 22.884 %w/w, while pyrolysis at C/F = 0.2 produced the highest monoaromatic contents of 20.274 %w/w. The best operating conditions, namely 60 minutes of pyrolysis with C/F = 0.05, resulted in an oil yield of 47.31 %w/w and an octane number of oil products of 80.645. These conditions produce oil with properties of kerosene fraction with a density of 0.778 g/mL and viscosity of 1.005 cSt.